Literature review of information security practice survey reports - Yang, Yaping (2018)
The author searched reports about enterprises information security prepared by consulting companies in order to understand organizations' security practices. The author then summarized the reports by year, identified topics such as the security relevant problems, firms' practices, policies, evolving technologies, etc. In the discussion section, perspectives or frameworks from academic literature were brought in.